Studi Keanekaragaman Vegetasi Riparian Rumput di Sepanjang Anak Sungai Bengawan Solo - Mentari Suri Insani; Murni Ramli; Ananda Tri Hapsari; Desrini Prapti Nurrohmah; Rahma Isnaini Puji Astuti; Viky Sabela Dewi Fortuna (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2025)
The Bengawan Solo River has an important role for humans and surrounding aquatic organisms. Efforts to maintain riparian vegetation can be done by maintaining the existence and striving for the diversity of constituent plant species so that they can provide services to the environment optimally. Therefore, this study aims to determine the diversity of riparian vegetation, especially grasses along Bengawan Solo tributaries. The research was conducted in February - July 2024 at three locations where the upstream was in the Bengawan Solo River, the middle of the river was in the Jatimalang River, and the downstream was in the Lalung Reservoir area, Karanganyar Regency. The method used in sampling is Purposive Random Sampling with the provision that each sample point plot has an area of 200 m2 made as many as 5 plots at each station. Observations include the name of the species and the number of individuals in each plot of each plant stata and the results obtained are then identified and calculated for diversity with the Shannon-Wiener index. The results obtained were fifteen (15) types of grass riparian vegetation belonging to three (3) tribes. The diversity of riparian vegetation at the grass level at the research site is moderate (H' 1≤ H ≤ 3).